Rock glaciers in Daxue Shan, south-eastern Tibetan Plateau: an inventory, their distribution, and their environmental controls - Ran, Zeze; Liu, Gengnian (The Cryosphere, 2018)
Rock glaciers are typical periglacial landforms. They can indicate the existence of permafrost, and can also shed light on the regional geomorphological and climatic conditions under which they may have developed. This article provides the first rock glacier inventory of Daxue Shan, south-eastern Tibetan Plateau. The inventory is based on analyses of Google Earth imagery. In total, 295 rock glaciers were identified in Daxue Shan, covering a total area of 55.70 km2 between the altitudes of 4300 and 4600 m above sea level. Supported by ArcGIS and SPSS software programmes, we extracted and calculated morphometric parameters of these rock glaciers, and analysed the characteristics of their spatial distribution within Daxue Shan. Our inventory suggests that the lower altitudinal boundary for permafrost across the eight aspects of observed slopes differs significantly and that the lower altitudinal permafrost boundary is ∼ 104 m higher on western than eastern-facing slopes. Moraine-type and talus-derived rock glaciers exhibit mean gradients that are all concentrated within the 22–35∘ range. However, lobate rock glaciers (27–45∘) have a higher mean gradient than tongue-shaped rock glaciers (22–35∘). Shady (i.e. N, NE, and E) slopes appear related to the presence of moraine-type rock glaciers, whereas sunny (i.e. W, SW, and S) slopes appear related to the presence of talus-derived rock glaciers. Rock glaciers in Daxue Shan are more concentrated within tertiary monzonitic granite, which is more sensitive than other lithological components to the freeze–thaw process. Continuous weathering of this substrate provides the ideal raw material for the rock glacier development. These results show that environmental controls (i.e. topographical, climatic, lithological factors) greatly affect the formation and development of rock glaciers. This study provides important data for exploring the relation between maritime periglacial environments and the development of rock glaciers on the south-eastern Tibetan Plateau (TP). It may also highlight the characteristics typical of rock glaciers found in a maritime setting.